Produksi dan Skrining Senyawa Metabolit sekunder Ecoenzyme Kulit Buah Jeruk BW dan Jeruk Siam yang Berpotensi sebagai Bioinsektisida - Budi Prasetyo; Hening Widowati; Agus Sutanto (Jurnal Penelitian Pertanian Terapan, 2024)
This study aims to determine the levels of secondary metabolites that have the potential as biopesticides in the ecoenzyme of BW and Siam orange peels. Research on making ecoenzymes was carried out in Karang Anyara Village, Labuhan Maringgai District, East Lampung Regency. Analysis of the levels of secondary metabolites was carried out at the Laboratory of Chemical Analysis, University of Muhammadiyah Malang, Malang City, East Java. Analysis of the levels of secondary metabolites of alkaloids, saponins, flavonoids, steroids, terpenoids, and tannins was carried out using the extraction-spectrophotometric method while the analysis of essential oil content was carried out by distillation method. The results of the study identified secondary metabolites with potential as bioinsecticides in the ecoenzyme of BW orange peel and Siamese orange peel. The compounds contained are alkaloids, saponins, flavonoids, steroids, terpenoids, tannins, and essential oils. The results of the Mann-Whitney test showed that there was a significant difference in the levels of secondary metabolites present in the ecoenzyme. To complete the results of this study, further research is needed to prove the effectiveness of using ecoenzyme from citrus fruit peels as a bioinsecticide. Keywords:, bioinsecticide, ecoenzyme, citrus peel